If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-4)=x-1/8
We move all terms to the left:
2(x-4)-(x-1/8)=0
We add all the numbers together, and all the variables
2(x-4)-(+x-1/8)=0
We multiply parentheses
2x-(+x-1/8)-8=0
We get rid of parentheses
2x-x-8+1/8=0
We multiply all the terms by the denominator
2x*8-x*8+1-8*8=0
We add all the numbers together, and all the variables
2x*8-x*8-63=0
Wy multiply elements
16x-8x-63=0
We add all the numbers together, and all the variables
8x-63=0
We move all terms containing x to the left, all other terms to the right
8x=63
x=63/8
x=7+7/8
| 2(x-4)=x-1/ | | Y=(2x-7)/3x | | /x^2=3x-1 | | (-8y-8)=9-4y+1 | | -(5z-3)/10=10 | | -x/5-4=8.8 | | Y(x)=65+5x | | -b-2.2=15.9 | | -a/2-5=8 | | 5v÷4=15 | | 9x-7=3-2x | | -b-10=-11 | | 5x+5=9x+5 | | x/12+2=8 | | 12(-42+40)=12(-8x+244) | | 3.2/0.2=a | | Y=x-0.04x2 | | y^2+12y=-116 | | 3/4(1/4x+8)-1/2x-2=3/8(4-x)-1/4x | | -4=-9/7a | | 4=7/2m | | 14z+5+6z=135 | | -1=2/5n | | 2x-39°=x | | 3=1/2a | | -3(-k-8)-3=29-k | | 1=-4/7b | | -0.7=-b/8 | | x+x-2+x-4=77 | | -2.9=y-11.1 | | x+x/2+x/4=77 | | 8x-2=4x+38 |